Armstrong's Axioms

ARMSTRONG'S AXIOMS

Armstrong axioms are a complete set of inference rules or axiomsThe inference rules are sound which is used to test logical inferences of functional dependencies. The Axioms are a set of rules, that when applied to a specific set, generates a closure of functional dependencies.

Armstrong's Axioms has two different sets of rules

1) Axioms or primary rules

Let suppose T (k) with the set of attributes k be a relation scheme. Subsequently, we will represent subsets of k as ABC. The standard notation in database theory for the set of attributes is AB rather than A∪B.

  1. Axiom of Reflexivity:
    If a set of attributes is P and its subset is Q, then P holds Q. If Q ⊆ P, then P → Q. This property is called as Trivial functional dependency. Where P holds Q (P → Q) denote P functionally decides Q.
  2. Axiom of Augmentation:
    If P holds Q (P → Q) and R is a set of attributes, then PR holds QR (PR → QR). It means that a change in attributes in dependencies does not create a change in basic dependencies. If P → Q, then PR → QR for any R.
  3. Axiom of Transitivity:
    If P holds Q (P → Q) and Q holds R (Q → R), then P hold R (P → R). Where P holds R (P → R) denote P functionally decides R, same with P holds Q and Q holds R.

2) Additional rules or secondary rules

These rules can be derived from the above axioms.

  1. Union:
    If P holds Q (P → Q) and P holds R (P → R), then P → QR. If X → Y and X → Z, then X → YZ.
  2. Composition:
    If P holds Q (P → Q) and A holds B (A → B), then PA → QB.
    proof,
    1. P → Q (Given)
    2. A → B (Given)
    3. PA → QA (Augmentation of 1 and A)
    4. PA → Q (Decomposition of 3)
    5. PA → PB (Augmentation of 2 and P)
    6. PA → B (Decomposition of 5)
    7. PA → QB (Union 4 and 6)
  3. Decomposition:
    This rule is contrary to union rule. If P → QR, then P holds Q (P → Q) and P holds R (P → R). If X → YZ, then X → Y and X → Z.
    proof,
    1. P → QR (Given)
    2. QR → Q (Reflexivity)
    3. P → Q (Transitivity of 1 and 2)
  4. Pseudo Transitivity:
    If P → RQ and Q → S, then P → RS.
    proof,
    1. P → RQ (Given)
    2. Q → S (Given)
    3. RQ → RS (Augmentation of 2 and R)
    4. P → RS (Transitivity of 1 and 3)

Post a Comment

0 Comments